Nitric oxide synthase-2 (CCTTT)n polymorphism is associated with local gene expression and clinical manifestations in patients with chronic rhinosinusitis. (1st January 2022) - Takemoto, Kota; Takeno, Sachio; Ishino, Takashi; Ueda, Tsutomu; Hamamoto, Takao; Horibe, Yuichiro; Takahara, Daisuke; Kawasumi, Tomohiro
Introduction: Nitric oxide (NO) is synthesized through NO synthase (NOS). The proximal NOS2 gene promoter contains the pentanucleotide CCTTT repeat polymorphism. We examined whether CCTTT repeats are associated with NOS2 expression in the sinonasal tissues and clinical manifestations in patients with chronic rhinosinusitis. Methods: Mucosal specimens were obtained from the ethmoid sinus and inferior turbinate of 30 eosinophilic chronic rhinosinusitis (ECRS) and 28 non-ECRS patients. CCTTT repeats were classified into short alleles (S), with less than or equal to 14, and long alleles (L), with more than 14. The subjects were classified into the L/S + L/L and S/S groups. Results: In ECRS, the NOS2 mRNA levels of the ethmoid sinus mucosa were significantly higher in the L/S + L/L group than in the S/S group (median, 1.66 and 0.77, respectively). On the ther hand, ECRS patients showed no significant difference in the NOS2 mRNA level of the inferior turbinate between the L/S + L/L group and the S/S group (median, 0.63 and 0.88, respectively). In ECRS, preoperative SNOT-22 were significantly higher in the L/S + L/L group than in the S/S group, whereas the former group showed a lower postoperative recurrence risk. Conclusion: CCTTT repeat polymorphism in the NOS2 promotor gene may be a useful indicator to evaluate ECRS severity and prognosis.